Freezing-Thawing Damage Mechanism of Coal Gangue Concrete Based on Low-Field Nuclear Magnetic Resonance, Scanning Electron Microscopy, and N2 Adsorption - Bowen Hou; Jisheng Qiu; Peng Guo; Xujun Gao; Ruyi Zhang (Advances in Civil Engineering)
To study waterborne frost heaving failure mechanism of coal gangue ceramsite concrete (CGCC) under freeze-thaw cycles, capillary water absorption test, nonmetallic ultrasonic testing test, low-field nuclear magnetic resonance (LNMR) test, N2 adsorption test, and other tests were used to determine the effect of freeze-thaw cycles on the porosity, relative dynamic elastic modulus (RDM), and capillary adsorption rate of different coal gangue ceramsite (MT) replacement rates (0, 20%, 40%, and 60%). Combining the changes of performance indexes and the changes of micropore structure under freeze-thaw cycles, the freeze-thaw failure mechanism of normal concrete (OC) and CGCC was analyzed. In view of the particularity of MT material, the method based on pore size is put forward to distinguish M pores from T pores, and the reasons for different properties are analyzed from the microperspective. The results show that the freeze-thaw cycle changes the microstructure of coal gangue concrete and has an obvious influence on its properties. And when the replacement rate is 40%, degradation mitigation performance is optimal. Due to the particularity of MT shape, T pores are dominant in coal gangue concrete matrix, which is different from the microstructure of ordinary concrete and can reduce the structural deterioration caused by freeze-thaw. The research results of this paper can provide a reference for the research and application of CGCC in freeze-thaw environment.